Związki Róży Luksemburg z Wrocławiem - Gelles, Katarzyna (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article concerns the affiliations of Polish socialist and German social democrat Rosa Luxemburg with Wrocław and party activists from this city. Wrocław played an important role in her political activities. She spoke in public in Wrocław several times and systematically collaborated with the local press organ of SPD (Sozialdemokratische Partei Deutschlands – Social Democratic Party of Germany) – “Volkswacht”. During the World War I, from July 1917 to November 1918, she was held in custody without trial in preventive detention in the Wrocław prison on present day Kleczkowska Street
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne